Clinical Neuroanatomy: A Neurobehavioral Approach - Mendoza, John E.; Foundas, Anne L. (Springer, 2008)
A major focus of clinical neuropsychology and cognitive-behavioral neurology is the assessment and management of cognitive and behavioral changes that result from brain injury or disease. In most instances, the task of the neuropsychologist can be divided into one of two general categories. Perhaps the most common is where patients are known to be suffering from identified neurological insults, such as completed strokes, neoplasms, major head traumas or other disease processes, and the clinician is asked to assess the impact of the resulting brain damage on behavior. The second involves differential diagnosis in cases of questionable insults to the central nervous system. Examples of the latter might be milder forms of head trauma, anoxia and dementia or suspected vascular compromise. In either instance, understanding the underlying pathology and its consequences depends in large part on an analysis of cognitive and behavioral changes, as well as obtaining a good personal and medical history. The clinical investigation will typically include assessing problems or changes in personality, social and environmental adaptations, affect, cognition, perception, as well as sensorimotor skills. Regardless of whether one approaches these questions having prior independent confirmation of the pathology versus only a suspicion of pathology, a fairly comprehensive knowledge of functional neuroanatomy is considered critical to this process. Unfortunately as neuropsychologists we too frequently adopt a corticocentric view of neurological deficits. We recognize changes in personality, memory, or problem solving capacity as suggestive of possible cerebral compromise. We have been trained to think of motor speech problems as being correlated with the left anterior cortices, asymmetries in sensory or motor skills as a likely sign of contralateral hemispheric dysfunction, and visual perceptual deficits as being associated with the posterior lobes of the brain. At the same time there should be an awareness that multiple and diverse behavioral deficits can frequently result from strategically placed focal lesions, and that many such deficits might reflect lesions involving subcortical structures, the cerebellum, brainstem, spinal cord, or even peripheral or cranial nerves. As first noted by Hughlings Jackson in the 19th century, while the cortex is clearly central to all complex human behavior, most cortical activities begin and end with the peripheral nervous system, from sensory input to motor expression. This current work was an outgrowth of seminars given by the principal author (JEM) at the request of neuropsychology interns and residents at the VA to broaden their clinical appreciation and application of functional neuroanatomy. In working closely with neurologists and neurosurgeons, these students also recognized the advantage of being able converse knowledgeably about patients with subtentorial deficits. While all the intricate details of the nervous system may be beyond the immediate needs of most clinicians, a general appreciation of its gross structural makeup and functional relationships is viewed as essential in working with neurological populations. To this end, the book begins with a brief review of the gross anatomy, functional correlates, and behavioral syndromes of the spinal cord and peripheral nervous system. From there, the text carries one rostrally, looking at these same features in the cerebellum, brainstem and cranial nerves. Where this volume deviates from most textbooks of functional neuroanatomy is in its expanded treatment of supratentorial structures, particularly the cerebral cortex itself, which more directly impacts on those aspects of behavior and cognition that often represent the primary focus or interests of neuropsychologists and behavioral neurologists.